Comparison Of Syntactic And Lexical Complexities In Research Articles By Iraqi And Non-Iraqi Writers - Al Sahlanee, Ali Yasir Fahad (2023)
Publication productivity is an essential metric of the performance of academics and higher learning. It is directly affecting institutions' ranking and reputation. Writing for publication is signified as high-quality writing that uses advanced complex lexical units and syntactic structures to convey complex scientific findings. Linguistic complexity investigates complexity at lexical and syntactic levels; it is perceived as a reliable indicator of writing quality, proficiency, and development. Given the issue of the low publication productivity of Iraqi writers in peer-reviewed international journals, this descriptive study was implemented to evaluate and compare the use of complex lexical items and syntactic structures in the writing of linguistics research articles (RAs) written by Iraqi, English second language (L2), and English first language (L1) writers. Using the Contrastive Rhetorical Theory underpinnings, the corpus of this study includes 150 linguistics RAs published in international journals indexed in the Scopus database, mainly 50 linguistics RAs each by Iraqi writers, English L2, and English L1 writers. This study followed Wood et al. (2001) criteria to classify English L1 and L2 writers. The texts were analysed using the Lexical Complexity Analyser (LCA) and Syntactic Complexity Analyser (SCA). The findings revealed that Iraqi writers utilised the lowest number of complex lexical items and syntactic structures in their RAs compared to the texts written by English L2 and L1 writers.